THE PRINCIPALITY OF WORKING WITH PARENTS IN IMPLEMENTING NATIONAL EDUCATION - Abdullajonova, Dildora (Журнал иностранных языков и лингвистики, 2023)
The article contains comments on the content and forms of providing national education to children in the family. It mainly includes the uniqueness of working with parents, the content of work related to raising their pedagogical level.